An Operational Framework for Managing Fiscal Commitments from Public-Private Partnerships - Shendy, Riham; Martin, Helen; Mousley, Peter (Washington, DC: World Bank, 2013)
The National policy on public-private partnerships (PPP) recently approved by the Government of Ghana (GoG) sets out the government's intention to use PPPs to improve the quality, cost-effectiveness, and timely provision of public infrastructure in Ghana. The PPP policy highlights the role of the government's financial support to PPPs, as well as the importance of putting in place a system to manage the associated fiscal commitments (FCs). As noted in the policy, the government's contribution to a PPP may include remuneration to the private party from government budgets, which may be fixed or partially fixed, periodic payments (annuities) and contingent. This report proposes an operational framework for managing fiscal obligations arising from PPPs in Ghana. This framework aims to ensure that PPP FCs are consistently identified and assessed during PPP project preparation, and that these assessments are fed into project approval. The report outlines roles and responsibilities, concepts, and processes for managing PPP FCs, drawing on international standards and practices, bearing in mind existing institutions and capacities in Ghana. The report also suggests legislative additions and capacity building needed to establish this framework in practice. This report focuses primarily on managing long-term FCs to PPPs, including regular payments or contingent liabilities (CL) that typically last throughout a project's lifetime. This report is structured as follows: chapter 1 is introduction; chapter; 2 introduces the concept of FCs from PPPs: how and why PPPs create FCs, why managing them is important, and an overview of what it entails; chapter 3 presents institutional roles and responsibilities; chapter 4 describes how FC management should be incorporated in the PPP development and approval process; chapter 5 describes how FCs can be managed during PPP implementation by monitoring, reporting, and budgeting adequately; and chapter 6 sets out the steps needed to begin to implement this PPP framework-to build its core requirements into the forthcoming PPP Law, and to build capacity in the relevant entities to carry out those requirements in practice.